(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
The paper aims at analysing the evolution of the connection between the Chinese political system and the local organised crime, in the form of triads. It focuses on the likely subordination of the triad societies to the Communist Party of China, above all in relation to the Hong Kong protests occurred in 2014 and in 2019.